500 curries : discover a world of spice in dishes from India, Thailand and South-East Asia, as well as Africa, the Middle East and the Caribbean, shown in 500 sizzling photographs - Baljekar, Mridula (Lorenz Books, 2010)
Offers a collection of 500 of the world's best curry dishes. This title features recipes for Beef Vindaloo, Chicken Satay and Coronation potatoes, Mussels Stuffed with Cinnamon-Spiced Pilaff, Spicy Aubergine Soup with Beef and Lime, and Malay Clay-pot Chicken